Microlearning to improve CPD learning objectives. (29th July 2020) - Prior Filipe, Helena; Paton, Morag; Tipping, Jane; Schneeweiss, Suzan; Mack, Heather G
SUMMARY: Background: Despite active involvement in teaching, clinical educators facilitating the continuing professional development (CPD) of their fellow specialists may not have formal training in medical education. Although required to write focused, measurable, topic‐relevant, attainable and time‐bound learning objectives to clearly inform learners on their learning intentions, CPD educators often receive no training on how to develop them. Microlearning is an online learning format occurring without real‐time or interpersonal interaction, aiming to deliver easily accessible small units of focused information that are readily applicable for professionals. We hypothesised that Portuguese ophthalmologist educators lecturing to their fellow specialists would benefit from a microlearning experience (MLE) to improve the quality of their learning objectives. Methods: We created an MLE about writing effective learning objectives. In phase 1, 25 clinical educators, scheduled to lecture at an ophthalmology conference in Portugal, were invited to watch the MLE, write and classify their learning objectives according to Bloom's modified taxonomy, and complete an evaluation survey. In phase 2, 86 clinical educators were invited to view the MLE and complete the survey. Results: In phase 1, 20% of participants completed the exercise and survey. They categorised their objectives high on Bloom's taxonomy, considered the MLE useful and stated their intent to apply the principles learned in practice. In phase 2, 29% of participants provided feedback. All agreed that the intervention was clear and useful and 87% expressed an intent to use this information in their educational practice. Conclusions: The majority of participants found the MLE clear and useful. Further studies are necessary to measure the impact of the MLEs used by clinical educators.